Requirements for Creating a Position for Community Health Nursing Within the Iranian Primary Health Care System: A SWOT Analysis - Hosseinnejad, Aazam; Rassouli, Maryam; Jahani, Simin; Elahi, Nasrin; Molavynejad, Shahram (Frontiers in Public Health, 2022)
Purpose: Accepting community health nursing in the primary care system of each country and focusing on creating a position for community health nurses is of significant importance. The aim of this study was to examine the stakeholders’ perception of the requirements for establishing a position for community health nursing in the Iranian primary health care system. Methods: This qualitative study was done using 24 semi-structured interviews conducted from May 2020 to February 2021 in Iran. The participants were selected through purposive sampling and consisted of nursing policy makers, the policy makers of the Health Deputy of Ministry of Health, the managers and the authorities of universities of medical sciences all across the country, community health nursing faculty members, and community health nurses working in health care centers. After recording and transcribing the data, data analysis was performed in MAXQDA10 software, using Elo and Kyngas’s directed content analysis approach and based on WHO’s community health nursing role enhancement model. The statements for each main category were summarized in SWOT classification. To examine the trustworthiness of the data, Lincoln & Guba’s criteria were used. Results: By analyzing the interviews 6 main categories identified consist of creating a transparent framework for community health nursing practice, enhancing community health nursing education and training for practice in the primary health care system and community settings, seeking support, strengthening the cooperation and engagement among the key stakeholders of the primary health care system, changing the policies and the structure of the health system, and focusing on the deficiencies of the health system.each main categories including the subcategories strengths, weaknesses, opportunities and threats (SWOT). Conclusions: One of the requirements for creating a position for community health nursing in the primary health care system of Iran is to pay attention to the above dimensions. If properly and correctly implemented within the sociocultural context of community, based on the primary health care system and in line with the actions and policies of the health care system, the above policies can help policymakers address challenges against community health nursing practice in the health system.